Therapeutic potential of a novel peripherally restricted CB1R inverse agonist on the progression of diabetic nephropathy - Jacquot, Laetitia; Pointeau, Océane; Roger-Villeboeuf, Célia; Passilly-Degrace, Patricia; Belkaid, Rim; Regazzoni, Isaline; Leemput, Julia; Buch, Chloé; Demizieux, Laurent; Vergès, Bruno; Degrace, Pascal; Crater, Glenn; et al. (Frontiers in Nephrology, 2023)
Objective This study assessed the efficacy of INV-202, a novel peripherally restricted cannabinoid type-1 receptor (CB1R) inverse agonist, in a streptozotocin-induced type-1 diabetes nephropathy mouse model. Methods Diabetes was induced in 8-week-old C57BL6/J male mice via intraperitoneal injection of streptozotocin (45 mg/kg/day for 5 days); nondiabetic controls received citrate buffer. Diabetic mice were randomized to 3 groups based on blood glucose, polyuria, and albuminuria, and administered daily oral doses for 28-days of INV-202 at 0.3 or 3 mg/kg or vehicle. Results INV-202 did not affect body weight but decreased kidney weight compared with the vehicle group. While polyuria was unaffected by INV-202 treatment, urinary urea (control 30.77 ± 14.93; vehicle 189.81 ± 31.49; INV-202 (0.3 mg/kg) 127.76 ± 20; INV-202 (3 mg/kg) 93.70 ± 24.97 mg/24h) and albumin (control 3.06 ± 0.38; vehicle 850.08 ± 170.50; INV-202 (0.3 mg/kg) 290.65 ± 88.70; INV-202 (3 mg/kg) 111.29 ± 33.47 µg/24h) excretion both decreased compared with vehicle-treated diabetic mice. Compared with the vehicle group, there was a significant improvement in the urinary albumin to creatinine ratio across INV-202 groups. Regardless of the dose, INV-202 significantly reduced angiotensin II excretion in diabetic mice. The treatment also decreased Agtr1a renal expression in a dose-dependent manner. Compared with nondiabetic controls, the glomerular filtration rate was increased in the vehicle group and significantly decreased by INV-202 at 3 mg/kg. While the vehicle group showed a significant loss in the mean number of podocytes per glomerulus, INV-202 treatment limited podocyte loss in a dose-dependent manner. Moreover, in both INV-202 groups, expression of genes coding for podocyte structural proteins nephrin (Nphs1), podocin (Nphs2), and podocalyxin (Pdxl) were restored to levels similar to nondiabetic controls. INV-202 partially limited the proximal tubular epithelial cell (PTEC) hyperplasia and normalized genetic markers for PTEC lesions. INV-202 also reduced expression of genes contributing to oxidative stress (Nox2, Nox4, and P47phox) and inflammation (Tnf). In addition, diabetes-induced renal fibrosis was significantly reduced by INV-202. Conclusions INV-202 reduced glomerular injury, preserved podocyte structure and function, reduced injury to PTECs, and ultimately reduced renal fibrosis in a streptozotocin-induced diabetic nephropathy mouse model. These results suggest that INV-202 may represent a new therapeutic option in the treatment of diabetic kidney disease.